2022
DOI: 10.3389/fimmu.2022.1006710
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence is a key mediator of lung aging and susceptibility to infection

Abstract: Aging results in systemic changes that leave older adults at much higher risk for adverse outcomes following respiratory infections. Much work has been done over the years to characterize and describe the varied changes that occur with aging from the molecular/cellular up to the organismal level. In recent years, the systemic accumulation of senescent cells has emerged as a key mediator of many age-related declines and diseases of aging. Many of these age-related changes can impair the normal function of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 145 publications
1
5
0
Order By: Relevance
“…Although torque tenovirus is highly detected in the BAL of patients with AE-IPF, the virus is not clearly related to disease progression (Wootton et al, 2011). Interestingly, studies report that epithelial cell dysfunction caused by cellular senescence may lead to increased bacterial and viral infections (Metzger and Sun, 2013;Torrance and Haynes, 2022). These findings concur with our hypothesis that pathogenic microbial infections, especially by bacteria, can easily occur in subtype S2, causing AE-IPF and poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Although torque tenovirus is highly detected in the BAL of patients with AE-IPF, the virus is not clearly related to disease progression (Wootton et al, 2011). Interestingly, studies report that epithelial cell dysfunction caused by cellular senescence may lead to increased bacterial and viral infections (Metzger and Sun, 2013;Torrance and Haynes, 2022). These findings concur with our hypothesis that pathogenic microbial infections, especially by bacteria, can easily occur in subtype S2, causing AE-IPF and poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…This will lead to a significant increase in age-related diseases. Aging has emerged as one of the greatest and most prevalent risk factors for the development of infectious diseases ( 1 , 2 ). However, it has been observed that individuals have a different pace of aging which led to the concept of biologic aging.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of a vaccine in the elderly population, therefore, depends on lower reactivity and number of antigen-presenting cells (APC), in particular of dendritic cells which tend to decrease with advancing age [ 6 ] but also show a reduction in functionality and consequently, a reduced production of interferon is observed [ 7 ]. The activation of T lymphocytes, in particular of CD8+ T lymphocytes, is also affected by the change linked to immunosenescence both in terms of a reduction in the absolute cell population and in a reduction in the various subsets with consequent functional alterations [ 8 ] such as a reduction in the production of cytokines [ 9 , 10 , 11 , 12 , 13 ]. B lymphocytes also undergo changes as a function of age which can be summarized in a reduced diversity and function of B cells and in the production of immunoglobulins during the activation of the humoral immune response [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%